2015
DOI: 10.1097/md.0000000000001725
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate Injection Versus Band Ligation in the Endoscopic Management of Acute Gastric Variceal Bleeding

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Also, hemostatic powder application had been studied on a small scale for such difficult bleeding situations as postbanding ligation ulcer 42 ; however, to date the only validated option in this situation is a high dose of proton pump inhibitors and injection of cyanoacrylate underneath the ulcer. 43…”
Section: Hemostatic Powdermentioning
confidence: 99%
“…Also, hemostatic powder application had been studied on a small scale for such difficult bleeding situations as postbanding ligation ulcer 42 ; however, to date the only validated option in this situation is a high dose of proton pump inhibitors and injection of cyanoacrylate underneath the ulcer. 43…”
Section: Hemostatic Powdermentioning
confidence: 99%
“…This material was used safely and effectively in various medical indications for obstructing digestive, urinary and pulmonary fistulas . Besides, it was used to ensure wounds, lacerations and corneal ulcer healing, mesh fixation for inguinal hernia and adhesion of bone or cartilage as well as to control bleeding from esophageal varices . CA converts into an inert polymer on coming in contact with moisture, solidifies within 5–10 s and fixes in a minute .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the rebleeding rate following EVO was significantly lower than that following EVL in patients with IGV1s (OR, 0.06; 95% CI, 0.01-0.58). 183 TIPS placement and EVO are both effective treatments to control bleeding, with a hemostasis rate of more than 90%. Because of complications such as HE, stent occlusion, and higher cost, TIPS placement over EVO is not recommended as a first-line treatment.…”
Section: Treatment Of Gov2 or Igv1 Bleedingmentioning
confidence: 99%
“…bleeding rate than EVL in patients bleeding from GOV1s (OR, 0.39; 95% CI, 0.16-0.94). 155,158,183 However, those studies included only a small number of patients. In a retrospective Korean study, EVO showed beneficial outcomes, with lower 1-year rebleeding rate (3.6% vs. 30.8%, P=0.004) and bleeding-related mortality rate (5% vs. 22%, P=0.05) than EVL.…”
Section: Prevention Of Rebleedingmentioning
confidence: 99%